Status of renewable energy resources for electricity supply in Ghana - Aboagye, Bernard; Gyamf, Samuel; Ofosu, Eric Antwi (Scientific African, 2020)
The Government of Ghana has defined key targets for its energy sector to provide electricity for all the citizens by the end of 2020. Renewable energy has been identified as one of the promising options for electricity generation in Ghana. Thus, Renewable Energy Act, 2011 (Act 882) was espoused to provide regulatory framework and monetary incentives to boost private sector investment and promote the use of renewable energy in efficient and sustainable manner. There is also a target to contribute 10% renewable energy (excluding large hydro) to the electricity generation mix by 2020. To achieve this target, the Government provides a lot of support for investment in renewable energy. This paper presents a comprehensive review of the status of renewable energy penetration in Ghana’s electricity supply mix after the Renewable Energy Act was adopted. The review mainly focused on renewable energy resources, current generation status and their applications, and ongoing renewable energy projects in Ghana, with comparative information from five countries spread across Africa; Kenya, Ethiopia, South Africa, Nigeria and Egypt, that are also focused on development of renewable energy resources. The review reveled that renewable energy resources abound in Ghana that could be promoted for economic development and reduce the negative effects of climate change. However, a small fraction of the renewable energy potential has been exploited for electricity supply despite the Government’s efforts to promote and increase renewable energy technologies in the country. The renewable energy target of 10% by the year 2020 is unlikely to be achieved as most of the policy instruments in the Renewable Energy Act could not be fully operationalised to boost renewable energy investment. The government has therefore, extended the 10% target to the year 2030 and has come up with Renewable Energy Master Plan with estimated investments required to achieve the target
Keywords: Ghana; Power; University of Energy & Natural Resources; ACE: Energy and Environmental Sustainability